Pandangan dan Dukungan Masyarakat Terhadap Kepemimpinan Kepala Desa Perempuan (Studi Kasus: Desa Taras Padang Kecamatan Labuan Amas Selatan Kabupaten Hulu Sungai) - Siti Nurhafizah; Zainul Akhyar; Suroto Suroto (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2021)
The purpose of this study is to determine the views and support of the society on women's leadership as village heads in Taras Padang Village. This study used qualitative research. Data sources were selected by purposive sampling with data collection techniques using observation, interviews and documentation. The data found were analyzed in three stages, namely data reduction, data presentation and verification. The results of this study indicated that: 1) the society's view of the leadership of women as Village Head in Taras Padang Village is influenced by historical factors of the fusion of village areas, primordial bonds, leadership styles and village development situations. 2) The society's support for the leadership of women as Village Heads in Taras Padang Village is influenced by gender, public interest and communication factors